Effect of Erythromycin on Orocecal Transit Time in Normal Healthy Male Subjects: A Double-Blind, Placebo Controlled Study - Anil Minocha; Steven H Gallo (Canadian Journal of Gastroenterology)
OBJECTIVE: To investigate the effect of erythromycin on orocecal transit time (OCTT) in 17 healthy male subjects in a double-blind, placebo controlled crossover trial.